Hukum Waris Adat Di Minangkabau Ditinjau Dari Kompilasi Hukum Islam Dan Hukum Perdata - Nova, Lena (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
The purpose of this research is to find out how the implementation of high and low heirloom inheritance systems in Minangkabau custom which is reviewed based on customary law, compilation of Islamic law and civil law and to see the common ground between the three laws. Which in the discussion the researcher examines based on related theories put forward by experts and empirical studies that have been carried out by previous researchers, both from academics and humanists. The approach method used in this research is mainly empirical normative. Empirical normative means identifying law as a real and functional social institution in a social life system in the context of creating a just life and guaranteed legal certainty. The data obtained from the literature research conducted a descriptive data analysis process in order to obtain a specific discussion of the phenomenon that was being raised in order to obtain appropriate conclusions. This research concludes that the inheritance system in high inheritance uses the matrilineal system, in which the heirs as the owner of the property are taken from the maternal line, but in practice, men have the same share. This explains that high inheritance only uses customary law, not KHI or the Civil Code. Low inheritance can use the Compilation of Islamic Law and Civil Law with the system adopted is bilateral, but in Minangkabau custom, low-grade inheritance can rise to high inheritance, if the heirs have agreed to apply the collective principle, namely inheritance is owned. along with not being distributed to individual heirs in order to maintain the integrity of the family and the inheritance of the parents